Potential energy yields of bioenergy crops in the tropics - Shin, S.; Bulusu, M.; Hartwig, A-M.; Ulrich, M.; Lee, S.M.; Baral, H.; Borchard, N. (Center for International Forestry Research, 2022)
Bioenergy can produce at least 25% of the global energy demand to combat climate change through reducing emissions in the energy sector. However, information on the bioenergy production potential of woody species and their suitability for silviculture on various soils in the humid tropics is limited. This slightly revised version of a short note published by Borchard et al. (2018) aims to identify tree species suitable for bioenergy production under these conditions. Data were compiled from 241 publications and nine freely available databases to assess environmental and silvicultural information on tropical tree species. Energy yield was derived from the estimated productivity of the reviewed species equivalent to an energy yield ranging between 2 and 444 GJ ha¯¹ yr¯¹. As such, these bioenergy yields are within the range reported for the lignocellulosic biomass of energy crops cultivated in Europe, the USA and Brazil. Our review identified some highyielding species (e.g., Dyera polyphylla (Miq.) Steenis, Metroxylon sagu (Rottb.), Pongamia pinnata (L.)) and leguminous species that could be beneficial in mixed stands (e.g., Elaeis oleifera (Kunth) and Pongamia pinnata) or are suitable species to grow on wet or re-wetted peatland (Dyera polyphylla). However, there are limitations to cultivating woody bioenergy species on wet peatland. Sustainable methods for managing and harvesting forests on wet or re-wetted peatland need to be developed.